Identification and characterization of proteins from Sabah edible seaweeds by using proteomics approach - Fisal Ahmad (2016)
The present study was carried out to examine the proteome profile of selected seaweed species from Sabah waters to explore their nutritional properties. Moisture content was a major component in seaweed followed by carbohydrate, mineral, and protein. The results showed significant differences (p<O.05) in proximate compositions and total phenolic contents among several species of red, green and brown seaweeds. Studies showed that red seaweed higher in carbohydrate (63 to 74 % dry weight) and protein (6 to 15 % dry weight) content. Brown seaweed higher in mineral (22 to 45 % dry weight) and fibre (21 to 45 % dry weight) content. Meanwhile, green seaweed higher in total phenolic content (48 to 52 mg PGE/g dry weight sample). Using caulerpa lentillifera, four different protocols for protein extraction were evaluated, namely: (i) no protein precipitation with fractionation; (ii) Trichloroacetic acid (TCA)-acetone precipitation; (iii) TCA-acetone precipitation with fractionation; and (iv) Phenol extraction methanolammonium acetate precipitation. Overall, the phenol extraction method gave a higher protein yield and some protein spots resolved with a satisfactory 2D-PAGE image quality than the other methods. Thus this method was used to extract total soluble protein from all 15 seaweed samples. There was a strong positive correlation between crude protein and total soluble protein concentration (r=O.952; p=O.007) in these fifteen varieties of seaweed. A distinctive protein pattern was observed in the SDS-PAGE gels between three different seaweed classes of green, red and brown colours. USing this method of extraction, it managed to get 2D-PAGE proteome map for three seaweeds species, namely caulerpa lentillifera, Kappaphycus alvareziivar. aring-aring and Sargassum polycystum. The image analysis of 2D-PAGE was performed with Progenesis SameSpots v 4.5 and four sets of comparison of the 2D-PAGE gel image were done, Set 1: caulerpa lentillifera fronds-CLB vs caulerpa lentillifera stolon-CLT; Set 2: Kappaphycus alvarezi; small branches-KAK vs Kappaphycus alvarezii big branches-KAB; Set 3: Sargassum polycystum vacuoles-SPB vs Sargassum polycystum leaves-SPD vs Sargassum polycystum stolon-SPT; and Set 4: caulerpa lentillifera-Q5 vs Kappaphycus alvarezii - KAS vs Sargassum polycystum -SPS to detect differentially expressed protein spot. Results of image analysiS revealed 77 differentially expressed proteins for experiment set of CLB vs. CL T, 98 differentially expressed proteins for experiment set of KAK vs. KAB, 93 differentially expressed proteins for experiment set of SPB vs. SPD vs. SPT and 148 differentially expressed proteins for experiment set of CLS vs. KAS vs. SPS. Only 20 differentially expressed proteins from all four sets of experiments have been successfully identified and characterized by using nano-LC-MS/MS (Orbitrap) and Bioinformatics Software PEAKS Studio 7. Most of the identified proteins were a non-enzyme protein such as light-harvesting phycobiliprotein, light-harvesting complex, histone, and elongation factor. The enzyme proteins identified were ribulose bisphosphate carboxylase and glyceraldehyde-3-phosphate dehydrogenase. Regarding health benefits, the potential evaluation of the peptide profile results showed that protein extracts from the three seaweeds species contain peptide sequences with a variety of beneficial health effects. From among 44 types of biological activity characteristics of peptides, as listed in the BIOPEP database, motifs with the Dipeptidyl Peptidase IV inhibitors and ACE inhibitory activity occur most frequently in all protein sequences from the seaweed samples. Others bioactive peptide present, such as antiOXidant, stimulating, regulating, antiamnestic, antithrombotic and many other activities. Therefore, this protein raw material, which currently remains a relatively untapped reservOir, has the potential to act as a resource for the generation of bioactive peptides with potential health-promoting and diseasepreventing properties. Hopefully, these findings will contribute towards seaweed protein utilization as alternative sources of peptide-based nutraceuticals for human health promotion.